2005
DOI: 10.1105/tpc.105.036806
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Functions as an Endogenous External Metabolite Regulating Plant Cell Viability

Abstract: ATP is a vital molecule used by living organisms as a universal source of energy required to drive the cogwheels of intracellular biochemical reactions necessary for growth and development. Animal cells release ATP to the extracellular milieu, where it functions as the primary signaling cue at the epicenter of a diverse range of physiological processes. Although recent findings revealed that intact plant tissues release ATP as well, there is no clearly defined physiological function of extracellular ATP in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
202
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(208 citation statements)
references
References 81 publications
4
202
0
2
Order By: Relevance
“…Moreover, that protoplasts could sustain the [Ca 2+ ] cyt elevation demonstrates that the wall is not critical for the response of this cell type. Previously, it had been suggested that wall proteins capable of phosphorylation intercept extracellular purine nucleotides to evoke a cellular response (Chivasa et al, 2005). The results also show that extracellular ADP can generate a [Ca 2+ ] cyt signal in the mature epidermis seemingly independently of heterotrimeric G-protein activity.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Moreover, that protoplasts could sustain the [Ca 2+ ] cyt elevation demonstrates that the wall is not critical for the response of this cell type. Previously, it had been suggested that wall proteins capable of phosphorylation intercept extracellular purine nucleotides to evoke a cellular response (Chivasa et al, 2005). The results also show that extracellular ADP can generate a [Ca 2+ ] cyt signal in the mature epidermis seemingly independently of heterotrimeric G-protein activity.…”
Section: Discussionsupporting
confidence: 60%
“…Extracellular purine nucleotides have been shown to be involved in the regulation of plant cell viability, membrane permeability, immunity, symbiosis, stress responses, and growth (Lew and Dearnaley, 2000;Tang et al, 2003;Chivasa et al, 2005Chivasa et al, , 2009Kim et al, 2006Kim et al, , 2009Roux and Steinebrunner, 2007;Wu et al, 2007;Riewe et al, 2008a;Wu and Wu, 2008;Yi et al, 2008;Demidchik et al, 2009;Govindarajulu et al, 2009;Kim et al, 2009;Clark et al, 2010aClark et al, , 2010bTanaka et al, 2010aTanaka et al, , 2010bTerrile et al, 2010;Tonó n et al, 2010). Purine nucleotide release from plant cells may occur through wounding, exocytosis, or through the activity of plasma membrane (PM) ATP-binding cassette transporters (Thomas et al, 2000;Kim et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that if the equilibrium between eATP accumulation at growth points and the removal of this eATP is disturbed by inhibition of ectoapyrase activity, the [eATP] rises to the point where growth becomes inhibited. On the other hand, extensive removal of eATP by application of high concentrations of potato (Solanum tuberosum) apyrase can lead to diminished growth (Kim et al, 2006) or even cell death (Chivasa et al, 2005). Taken together, these data predict that there is an optimal level of eATP that can stimulate superoxide production leading to growth promotion, but significantly higher or lower levels would turn on alternative pathways leading to growth inhibition.…”
Section: Discussionmentioning
confidence: 73%
“…Plasma membrane-associated apyrases in plants could, in principle, function as ectoapyrases because plant cells, like animal cells, release significant quantities of ATP into their ECM when they are mechanically stimulated (Jeter et al, 2004), when they are wounded , and when they are engaged in activities that involve active secretion, such as growth (Kim et al, 2006). Moreover, control of this eATP could be important because plant cells have significant signaling responses to submicromolar ATP (Demidchik et al, 2003;Song et al, 2006) and extensive depletion of eATP can result in loss of cell viability (Chivasa et al, 2005).…”
mentioning
confidence: 99%